PROJECT-BASED LEARNING IN TEACHING GRAMMAR FOR HIGH AND LOW MOTIVATED STUDENTS The Case of The Tenth Graders of Sman 1 Bangsri In The Academic Year of 2013/2014 (Universitas Negeri Semarang, 2014)
Although the present body of literature supports the use of project-based learning (PBL) to teach grammatical accuracy, there is still huge urgency to investigate its effectiveness for language learners with different motivation. This study aims to investigate the effectiveness of PBL, the effect motivation in teaching grammar for ten graders and the interaction among techniques, motivation, and students’ grammar. The study is a 2X2 factorial research design involving 48 students in two experimental groups and two control groups. The samples are divided into high and low motivated where the experimental groups are taught using PBL and the control groups are taught using collaborative learning. The data are collected by using a pretest and a posttest. Statistical Package for Social Sciences (SPSS) is used for analyzing the data. The content analysis reveals that students’ motivation does not effect students grammar significantly in both experimental and control groups. The finding also shows that both techniques are effective to improve students’ grammatical accuracy for high and low motivated students. The analysis of variance shows that there is no interaction among students’ motivation, techniques, and students’ grammar with the level of significance at 0.934. The study suggests that teachers must be able to consider the presence of both variables in teaching and learning, especially to teach grammatical accuracy.